Grammatical Relation: Subject Constructions in Batak Toba Language - Rezeki, Tri Indah; Mulyadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to delineate the grammatical relations within the Toba Batak language, explicitly focusing on characterizing the behavioral properties of subject construction. Employing a descriptive qualitative research approach, this study drew its data from 14 songs in the Toba Batak language retrieved from the social media platform YouTube, containing instances of grammatical relations, particularly those undergoing subject construction examination. The data collection process involved listening to and recording song lyrics in the Toba Batak language. Within these songs, the identified subject constructions undergoing testing include the Subject of quantifier float (